A CMOS balun with common ground and artificial dielectric compensations applied in a wideband RF front-end. (July 2022) - Yang, Geliang; Tang, Kai; Wang, Zhigong
Abstract: This paper presents a compact on-chip balun with a turn ratio of 1:2, and its application for sub-6 GHz wideband front-end. The common ground between the primary and secondary windings is designed by utilizing a short transmission line (T-line) to eliminate the imbalance. To further mitigate the imbalance, float metal conductors are used as a part of primary winding for artificial dielectric compensation. A 2.0-to-3.7 GHz wideband RF front-end is also designed by using the proposed CMOS balun. The balun and RF front-end are fabricated by using a standard 0.13-μm CMOS technology. The bandwidth of the proposed balun for |S11|<-10 dB is 2.2–5.1 GHz with fractional bandwidth up to 79.5%. In the operational bandwidth, the maximum amplitude and phase imbalance is 1.5 dB and 2°, respectively. The measured insertion loss is 4.8–5.6 dB (including 3 dB splitting loss) within the frequency range from 2.2 to 5.1 GHz.